Buckling of broad, anchored, cylindrical liquid-storage tanks subjected to horizontal ground motion. - Boutros, Tony. (University of Ottawa (Canada), 1998)
The study of the seismic response of broad, anchored, cylindrical liquid-storage tanks has large practical significance because these structures are used in many critical engineering applications (petroleum industries, nuclear power stations, municipal water supply systems, wine industries ...). The performance of such tanks during recent earthquakes and in experiments has indicated that the existing codes for designing tanks are in need of improvement. Due to the complexity of the dynamic analysis, several researchers have used a static approach to predict the dynamic buckling load. It has been demonstrated that such a static analysis yields useful information. On the basis of this finding, an approximate analytical method is developed to study the buckling of broad, anchored, cylindrical liquid-storage tanks subjected to horizontal ground motion. The solution is based on the linearized Donnell's shell stability equations and Galerkin's approach. The smallest buckling load (or the critical load factor) is calculated using the inverse iteration method. Theoretical results are then determined for two cases of broad tanks presented as examples. The validity of the findings of the present work is checked through comparison with results obtained by the numerical Finite Element Method (FEM).
Keywords: Engineering, Civil.